CANADIAN EXPERTISE IN AGING, A SUPPLY CHAIN MANAGEMENT ISSUE?. (11th November 2018) - Madden, K M; Hogan, D; Borrie, M
Abstract: Like most western countries, Canada is undergoing a steep demographic shift, despite attempts to mitigate this issue through increased immigration. This demographic shift can be shown by changes in the median age of Canadians. In 1956, the median age in Canada was 27.2 years, climbing to 39.5 in 2006 and is expected to reach 46.9 by 2056. Such large demographic shifts make it difficult to meet the demand for both academic and clinical gerontology expertise. Although difficult to quantify, the current supply of aging experts is sorely lacking. A national effort has been expended to increase training, but the distribution of such highly recruited experts has become quite uneven. For example, a single hospital in Vancouver has 9 geriatric medicine specialists, while there is only one geriatrician in the entire province of Saskatchewan. Future workforce planning strategies need to focus both on distribution and quantity of expert personnel.